Answer:
y =
x² - x +
![(7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/swja8pzsi6z73pv8hxa1nnp3vik90mp30r.png)
Explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Here (h, k) = (1, 3 ), thus
y = a(x - 1)² + 3
To find a substitute (- 1, 5) into the equation
5 = a(- 1 - 1)² + 3 ( subtract 3 from both sides )
2 = 4a ( divide both sides by 4 )
a =
, thus
y =
(x - 1)² + 3 ← expand factor using FOIL
y =
(x² - 2x + 1) + 3 ← distribute parenthesis
=
x² - x +
+ 3
=
x² - x +
![(7)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/swja8pzsi6z73pv8hxa1nnp3vik90mp30r.png)